Interaction of modified celluloses and pectins with gluten proteins - Correa, María Jimena (2014)
Physical and chemical techniques were applied to characterize the type of interaction between hydrocolloids and the gluten network in wheat dough, with and without NaCl. Modified celluloses (microcrystalline cellulose, MCC; carboxymethylcellulose, CMC, hydroxypropylmethylcelluloses, HPMC) and pectins of low (LMP) and high (HMP) degree of methylation were utilized as hydrocolloids to interact with gluten proteins. Modified celluloses were employed at 1.5% (flour basis) and pectins at 2.0% (flour basis). By microscopy (SEM and CLSM), it could be observed that NaCl induced a more marked crosslinking and orientation of gluten network. On the other hand, the addition of hydrocolloids led to more open matrices. Molecular mobility was evaluated by 1H-NMR assays and significant effects of NaCl addition and hydrocolloid type were found on relaxation times (T2). In presence of salt, significantly higher relaxation times were observed when modified celluloses were added. Hydrocolloid addition strongly affected the secondary conformation of proteins as studied by FT-Raman. In absence of NaCl, control and MCC samples exhibited the higher α-helix conformation percentage (indicating a more ordered and compact structure), followed by dough with HMP, HPMCs, LMP and CMC. In general, doughs with modified celluloses and NaCl showed a decrease of α-helix conformation. CMC dough showed the smallest percentage of α-helix conformation, and the highest contributions of more unfolded structures. Doughs with pectins and NaCl showed similar percentages of α-helix to control one but an increase of random coil structure was observed. Electrophoresis assays confirmed that the presence of certain hydrocolloids (CMC) during gluten formation could affect protein interaction promoting subunits lability from the matrix.